Compression ignition of low-octane gasoline: Life cycle energy consumption and greenhouse gas emissions. (1st November 2016) - Hao, Han; Liu, Feiqi; Liu, Zongwei; Zhao, Fuquan
Highlights: A process-based, well-to-wheel conceptualized life cycle assessment model is established. The impacts of using low-octane gasoline on compression ignition engines are examined. Life cycle energy consumption and GHG emissions reductions are 24.6% and 21.6%. Significant technical and market barriers are still to be overcome. Abstract: The use of low-octane gasoline on Gasoline Compression Ignition (GCI) engines is considered as a competitive alternative to the conventional vehicle propulsion technologies. In this study, a process-based, well-to-wheel conceptualized life cycle assessment model is established to estimate the life cycle energy consumption and greenhouse gas (GHG) emissions of the conventional gasoline-Spark Ignition (SI) and low-octane gasoline-GCI pathways. It is found that compared with the conventional pathway, the low-octane gasoline-GCI pathway leads to a 24.6% reduction in energy consumption and a 22.8% reduction in GHG emissions. The removal of the isomerization and catalytic reforming units in the refinery and the higher energy efficiency in the vehicle use phase are the substantial drivers behind the reductions. The results indicate that by promoting the use of low-octane gasoline coupled with the deployment of GCI vehicles, considerable reductions of energy consumption and GHG emissions in the transport sector can be achieved. However, significant technical and market barriers are still to be overcome. The inherent problems of NOx and PM exhaust emissions associated with GCI engines need to be further addressed with advanced combustion techniques. Besides, the yield of low-octane gasoline needs to be improved through adjusting the refinery configurations.